La inteligencia artificial en la contratación pública: Marco jurídico para su adquisición y aplicación en los procesos de compra - Vázquez Matilla, Francisco Javier (Pontificia Universidad Católica del Perú, 2025)
This paper addresses artificial intelligence (AI) both as a tool to support contract management and as a direct object of public procurement. From this latter perspective, it examines the legal, technical and operational risks involved in acquiring AI systems, particularly regarding interoperability, data protection and competition. Based on the Spanish and EU regulatory frameworks, the paper identifies key elements for promoting ethical, innovation-friendly procurement. These include preliminary market consultations, project competitions, regulatory sandboxes and results-oriented service level agreements aimed at enhancing competition and facilitating the participation of SMEs and startups.

Este trabajo aborda la inteligencia artificial (IA) tanto como herramienta de apoyo a la gestión contractual como objeto directo de adquisición por las administraciones. Desde esta segunda perspectiva, se analizan los riesgos jurídicos, técnicos y operativos que implica su compra, en especial en relación con la interoperabilidad, la protección de datos y la competencia. A partir del marco normativo español, se proponen claves para una contratación ética y abierta a la innovación. Entre ellas, destacan las consultas preliminares al mercado, concursos de proyectos, sandboxes regulatorios, acuerdos de nivel de servicio orientados a resultados así como facilitar la participación de PYMEs y startups.
Artificial intelligence in public procurement: Legal framework for its acquisition and application in purchasing processes
Keywords: Artificial Intelligence; Public Procurement; Interoperability; Ethic; Competition; Innovation; RIA; GovTech; Administrative Law; Spain; Inteligencia Artificial; Contratación Pública; Interoperabilidad; Ética; Competencia; Innovación; RIA; GovTech; Derecho Administrativo; España; https://purl.org/pe-repo/ocde/ford#5.05.00